Fostering Human Capital Development Through the Triple Helix Model of Innovation: Cases from Selected Local Colleges and Universities (LCUs) in Metro Manila - Juvy B. Hermosura (Iapa Proceedings Conference, 2019)
This study attempts to provide a modest contribution in the field of public administration by giving emphasis on human capital development which can be made possible through industry-academe-government collaboration otherwise known as the triple helix model of innovation. This model shows the dynamics arising from the interactions between the three principal institutional spheres in an economy – academe, government, and industry. The study examines the various partnership initiatives of identified Local Colleges and Universities (LCUs) in Metro Manila aimed at producing better quality graduates who can contribute to economic development. Using desk study and Key Informants Interview (KII) in gathering data, it was found out that LCUs are already into various engagements with the industry though still very limited as the usual partnership modes cited are on internship, scholarship, physical resources sharing, and faculty training. There are only few programs jointly designed by the university and industry with government participation but can be a good benchmark for other LCUs and local government units. The study draws the following suggestions for policy consideration: to promote triple helix model of innovation in human capital development programs; flexibility to design courses relevant to the community; government incentives for companies collaborating with universities; institutionalization of industry practitioners involvement in curriculum development; provision of timely and usable labor market data; and creation of LCUs particularly in the provinces and capacitating them using the triple helix model.